Ilmu Sharaf Dalam Perspektif Semantik: Analisis Makna Nakirah dan Ma’rifat Melalui Teori Referensial - Rofii, M (STAI Syaichona Moh. Cholil Bangkalan, 2025)
This research investigate the concept of nakirah and ma'rifat in sharaf through a semantic approach, especially referential theory. Sharaf as a branch of Arabic language science has an important role in understanding the structure and form of words, while semantics provides a more contextual and philosophical approach to meaning. By utilizing referential theory, this research aims to explore how nakirah and ma'rifat word forms not only have grammatical differences, but also demonstrate referential relationships in linguistic context. The research method used is a qualitative approach with descriptive analysis of a number of Arabic texts in sharaf books. The results indicate the nakirah form tends to show a meaning is general and not specific, while ma'rifat leads to a meaning is more certain and identified. These findings enrich the understanding of the dynamics of meaning in the morphological structure of Arabic and show the relevance of integration between the science of sharaf and semantic theory in Arabic linguistic studies. Therefor, the interpretation of a word's meaning depends not only on its grammatical form, but also on the accompanying context.